Viral Aetiology of Acute Flaccid Paralysis Surveillance Cases, before and after Vaccine Policy Change from Oral Polio Vaccine to Inactivated Polio Vaccine - T. S. Saraswathy Subramaniam; Mohd Apandi Apandi; Rohani Jahis; Mohd Samsul Samsudin; Zainah Saat (Journal of Tropical Medicine)
Since 1992, surveillance for acute flaccid paralysis (AFP) cases was introduced in Malaysia along with the establishment of the National Poliovirus Laboratory at the Institute for Medical Research. In 2008, the Ministry of Health, Malaysia, approved a vaccine policy change from oral polio vaccine to inactivated polio vaccine (IPV). Eight states started using IPV in the Expanded Immunization Programme, followed by the remaining states in January 2010. The objective of this study was to determine the viral aetiology of AFP cases below 15 years of age, before and after vaccine policy change from oral polio vaccine to inactivated polio vaccine. One hundred and seventy-nine enteroviruses were isolated from the 3394 stool specimens investigated between 1992 and December 2012. Fifty-six out of 107 virus isolates were polioviruses and the remaining were non-polio enteroviruses. Since 2009 after the sequential introduction of IPV in the childhood immunization programme, no Sabin polioviruses were isolated from AFP cases. In 2012, the laboratory AFP surveillance was supplemented with environmental surveillance with sewage sampling. Thirteen Sabin polioviruses were also isolated from sewage in the same year, but no vaccine-derived poliovirus was detected during this period.